Communication theory for everybody a handbook - Henson, Mari J.; Yogyog, Leah Carissa A. (Quezon City Giraffe Books, 2004)
Contents: Definitions and theories of communication. Aspects of communication. Kinds and styles of communication. Applications. Glossary. Recommended readings. Selected titles from Giraffe Books.
Purpose: "It explains and makes communication theory comprehensible to the readers; and it enables the reader to use communication as a tool and equipment for living and functioning in the Information Age."
Keywords: Communication -- Handbooks, manuals, etc